Portrait de l’artiste en jeune femme : Wormwood (1890) de Marie Corelli - Laurence Talairach-Vielmas (Cahiers Victoriens et Edouardiens)
Unlike her famous gothic romances and her melodramas, Marie Corelli’s Wormwood (1890) hinges upon the fin-de-siècle cultural context. In this novel, Corelli’s main character is an absintheur, and the plot unravels in Paris where decadent artists indulge in drugs. France then becomes an apt screen on which to project fin-de-siècle anxieties and to denounce immorality. This time, Corelli’s moralizing vignettes are two-fold. She uses absinth to criticize degeneration both in society and in art, denouncing naturalism — a literary genre known to be written by men for men, thereby suggesting that women can only write domestic novels. Thus Corelli seeks to impose her own voice by dealing with naturalistic issues and by featuring a female artist who refuses drugs and despises decadence. As male and female artists compete throughout the novel, they illustrate the literary debates of the 1880s and 1890s, and show how Corelli manages to handle a literary genre from which women were excluded.